Seasonal Variation, Chemical Composition and Antioxidant Activities of Ascophyllum Nodosum - Anna Þóra Hrólfsdóttir 1992- (2021)
Ascophyllum nodosum has been harvested and processed into algal meal in Breiðafjörður for over 40 years with hardly any innovation. The meal is mostly sent out of the country for alginate production, where other compounds in the meal, including bioactive compounds, get waisted. Hence, the aim of the study was to investigate chemical and bioactive characteristics of Ascophyllum nodosum and to evaluate the potential benefits of processing a press liquid as a side product during the production of algal meal. It was done by examining the seasonal variation of A. nodosum (sampling in June, July and October), studying the chemical composition (moisture, fat, protein, ash and salt) and trace minerals (iodine, arsenic, mercury, cadmium and lead) changes occurring during processing by analysis of fresh seaweed, press liquid, marc and algal meal. The antioxidant activities (ORAC, DPPH and MC) and TPC of the press liquid extract were analyzed and compared to extracts made with traditional water extraction methods. The results indicated that the chemical composition of Ascophyllum nodosum is linked to both the seasonal variation and the reproductive state of the algae. The fresh seaweeds sampling in June contained higher content of moisture, ash, protein and fat when compared to the other harvesting periods. The TPC and ORAC were lowest in June, but similar results were obtained in both measurements for the other two harvesting periods. The extracts were high in DPPH, or over 75% inhibition in all cases, and the metal chelating ability was not affected by harvesting time. Pearson’s correlation showed a relationship between TPC and ORAC (r=0.8), but the TPC did not correlate to the other assays. Production of press liquid as a side product in algal meal production is an option that is worth looking at but needs further research with respect to mineral content and polysaccharide composition in the production process. Matvælasjóður